Revisiting Hegel’s Philosophy of Religion. Stewart, J. (2022). An Introduction to Hegel's Lectures on the Philosophy of Religion: The Issue of Religious Content in the Enlightenment and Romanticism. Oxford: Oxford UP. - Kravchenko, Alexey (Sententiae, 2022)
Review of Stewart, J. (2022). An Introduction to Hegel's Lectures on the Philosophy of Religion: The Issue of Religious Content in the Enlightenment and Romanticism. Oxford: Oxford UP